Corporate acquisitions and mergers in Germany - Doll, Natascha (Kluwer Law International, 2021)
Derived from Kluwer?s multi-volume 'Corporate Acquisitions and Mergers', this work provides a concise, practical analysis of current law and practice relating to mergers and acquisitions of public and private companies in Germany. The book offers a clear explanation of each step in the acquisition process from the perspectives of both the purchaser and the seller. Key areas covered include: structuring the transaction; due diligence; contractual protection; consideration; and the impact of applicable company, competition, tax, intellectual property, environmental and data protection law on the acquisition process.